2002
DOI: 10.1001/archinte.162.5.553
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Acute Myocardial Infarction Among Patients Treated at Sites With and Without On-site Availability of Angiography

Abstract: In the early post-AMI period, the QOL of patients admitted at sites with angiography was higher than that of patients admitted at sites without angiography. However, by 1 year, the QOL and functional status of patients was similar in both groups. Differences in QOL were greatest when differences in treatment were greatest, lending support to a positive albeit small association between an early invasive approach to post-AMI care and improved QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
3
18
0
2
Order By: Relevance
“…Others studies [38,39,[41][42][43] found similar results. Spertus et al (2006) showed that incidence of angina pectoris in patients before performing the PCI is important predicative factor of the HRQL after the PCI, as well as the age and the physical function.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Others studies [38,39,[41][42][43] found similar results. Spertus et al (2006) showed that incidence of angina pectoris in patients before performing the PCI is important predicative factor of the HRQL after the PCI, as well as the age and the physical function.…”
Section: Discussionsupporting
confidence: 74%
“…Patients who had undergone PCI had significantly faster recovery in the early postinfarction period, higher reduced of chest pains and a higher HRQL compared with patients who were treated with thrombolytic therapy [38,39,[41][42][43]. Spertus et al (2003) believes that one of the most common indication for implementation of percutaneous coronary reperfusion is to improve the HRQL of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…toward health status outcomes as being equally, if not more, important for the well-being of patients with cardiac disease (1)(2)(3)(4). Little is known about the determinants of health status in patients with cardiovascular disease (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of such patients have examined the contribution of a wide range of sociodemographic, vocational, and medical variables to these patients’ reemployment. A survey of empirical studies of the qualitative and quantitative aspects of employment after an AMI, published between 1988 and 2003, uncovered 46 investigations [3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48]. An examination of these investigations revealed the following limitations: (1) most studies involved selected samples of participants (e.g., randomized intervention studies), (2) most studies examined employment within the first year after AMI, (3) most studies did not distinguish between employment status, resumption of employment, and maintenance of employment, (4) few studies investigated long-term maintenance of employment after AMI, (5) few studies were longitudinal community cohort studies, and (6) most studies included participants who had reached an age at which employment is no longer central.…”
Section: Introductionmentioning
confidence: 99%